Aging Leads to a Dysregulation in Mechanically Driven Bone Formation and Resorption. (1st May 2015) - Razi, Hajar; Birkhold, Annette I; Weinkamer, Richard; Duda, Georg N; Willie, Bettina M; Checa, Sara
ABSTRACT Physical activity is essential to maintain skeletal mass and structure, but its effect seems to diminish with age. To test the hypothesis that bone becomes less sensitive to mechanical strain with age, we used a combined in vivo/in silico approach. We investigated how maturation and aging influence the mechanical regulation of bone formation and resorption to 2 weeks of noninvasive in vivo controlled loading in mice. Using 3D in vivo morphometrical assessment of longitudinal microcomputed tomography images, we quantified sites in the mouse tibia where bone was deposited or resorbed in response to controlled in vivo loading. We compared the (re)modeling events (formation/resorption/quiescent) to the mechanical strains induced at these sites (predicted using finite element analysis). Mice of all age groups (young, adult, and elderly) responded to loading with increased formation and decreased resorption, preferentially at high strains. Low strains were associated with no anabolic response in adult and elderly mice, whereas young animals showed a strong response. Adult animals showed a clear separation between strain ranges where formation and resorption occurred but without an intermediate quiescent "lazy zone". This strain threshold disappeared in elderly mice, as mechanically induced (re)modeling became dysregulated, apparent in an inability to inhibit resorption or initiate formation. Contrary to what is generally believed until now, aging does not shift the mechanical threshold required to initiate formation or resorption, but rather blurs its specificity. These data suggest that pharmaceutical strategies augmenting physical exercise should consider this dysfunction in the mechanical regulation of bone (re)modeling to more effectively combat age‐related bone loss. © 2015 American Society for Bone and Mineral Research.